An analysis of mathematics textbook of Indonesian curriculum based on functional thinking framework - Prabawanto, Sufyani; Utami, Nadya Syifa; Dahlan, Jarnawi Afgani (JRAMathEdu (Journal of Research and Advances in Mathematics Education), 2023)
Functional thinking (FT) is individual’s cognitive process to identify the relation between variables and is essential for students to learn algebra. However, not much studies addressing the examination of the contents of FT problems within school mathematics textbooks, particularly in Indonesian curriculum. This study aims to describe the mathematics problems presented in junior high school mathematics textbooks of the new Indonesian curriculum (Kurikulum Merdeka) based on the FT framework. To reach this aim, the student mathematics textbook published by The Ministry of Education, Culture, Research, and Technology (Kemdikbud) in 2022 was used to conduct the analysis. The textbooks used were seventh and eighth-grade mathematics textbooks. The data was collected by observing the textbook's contents in the algebra domain. The analysis was based on the framework of FT consisting of recursive patterns, covariance, and correspondence. The results show that the FT tasks appear in the learning of algebraic terms, modelling with algebra, and linear functions. Moreover, this study also found that tasks in each topic develop students’ FT at different stages. Tasks in algebraic terms fulfill all FT’s stages in hierarchical order, tasks in modelling with algebra focus on the correspondence stage, and tasks in linear functions include all FT stages but not in chronological order; that is, recursive patterns, correspondence, and then covariation. In conclusion, this study finds that algebraic problems provided by Indonesian textbooks already support students’ FT. Thus, designing more FT tasks and connecting each task to different algebra topics might help students develop their FT.